Building beautiful bridges: Indigenous womxn artists using social networking sites to address violence - Folsom, Jennifer J., author; Wolfgang, J. David, advisor; Arthur, Tori Omega, committee member; Champ, Joseph G., committee member; Jacobs, Peter, committee member; Moore, Emily L., committee member (Colorado State University. Libraries, 2022)
Using Indigenous aesthetics, critical technocultural discourse analysis, and Indigenous storyworks, this study explores how Indigenous womxn's art practices challenge settler-colonizing visual and media representations of Indigenous peoples that feed violence against womxn, girls and two-spirits; and in the digital realm, how sharing their art-stories is testimony to the unique voices of Indigenous womxn's leadership. A critical technocultural discourse analysis of in-depth interviews and social networking site (SNS) posts reveals underlying settler-colonial discourses. Through their art-storytelling, artist-participants use technocultural discourses of generosity, collaboration/reciprocity, calling in/calling out, creating and respecting boundaries and fierceness to shift dominating discourses. In a real sense they are building bridges between on and offline realms, strengthening community networks, and bringing together past, present and future to prevent violence.
Keywords: #mmiwg2s; Indigenous art; social media; critical technocultural discourse analysis; #mmiw; Indigenous storyworks